Hadith of Leadership in Islam - Mohammad Abdul Al Halib; Uus Husni Hoer; Erna Robiatul Adawiah; Muhammad Wildan Nf; Putri Hafidzah (Taqriri: Journal of Al-Hadith Science Studies, 2025)
A leader is someone who has great responsibility in either an organization, a country or a kingdom. Islamic leadership is a balance of leadership with the concept of the world and the hereafter.  Islamic leadership prioritizes the values ​​proposed by Islam and also everything that is done in hope of Allah's blessing. This journal aims to educate readers, especially writers, which will be conveyed in this journal, namely the understanding, sources of leadership teachings (Al-Quran, hadith), basic principles of leadership, ideal qualities of a leader, and the role and responsibilities of a leader. in Islam